The role of prefrontal cortex in the control of feature attention in area V4 - Narcisse P. Bichot (Nature Portfolio, 2019)
The neural mechanisms underlying feature based attention to targets in a cluttered scene are not well understood. Here, the authors show that inactivation of the ventral prearcuate region leads to deficits in picking out a target among many stimuli as well as eliminates the feature based modulation of responses of V4 neurons.